2014
DOI: 10.4103/0972-0707.128063
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of acceptance, preference and efficacy between pressure anesthesia and classical needle infiltration anesthesia for dental restorative procedures in adult patients

Abstract: Introduction:Intraoral local anesthesia is essential for delivering dental care. Needless devices have been developed to provide anesthesia without injections. Little controlled research is available on its use in dental restorative procedures in adult patients. The aims of this study were to compare adult patients acceptability and preference for needleless jet injection with classical local infiltration as well as to evaluate the efficacy of the needleless anesthesia.Materials and Methods:Twenty non fearful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
14

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 17 publications
(33 reference statements)
3
44
0
14
Order By: Relevance
“…One clinical trial determined that the mean pulpal anesthetic duration for the traditional technique is 50±9.32 minutes (p>0.001) with a short needle and carpule syringe, whereas the jet injection technique resulted in the lowest duration of 20±3.53 minutes (p>0.001) 25 . These results are consistent with the findings of our study.…”
Section: Discussionsupporting
confidence: 91%
“…One clinical trial determined that the mean pulpal anesthetic duration for the traditional technique is 50±9.32 minutes (p>0.001) with a short needle and carpule syringe, whereas the jet injection technique resulted in the lowest duration of 20±3.53 minutes (p>0.001) 25 . These results are consistent with the findings of our study.…”
Section: Discussionsupporting
confidence: 91%
“…When the patients were asked about the form of anesthesia they prefer 17 patients out of 30 (56.7%) preferred EMLA, 10 patients out of 30 (33.3%) preferred Madajet XL which was in accordance with the two different studies conducted by Steenberghe DV 2 and Makade CS et al 22 Steenberghe DV 2 when compared anesthetic gel with injection anesthesia, he found that 70% of the patients preferred anesthetic gel while only 22% of the patients preferred injection anesthesia. Makade CS et al 25 when compared pressure anesthesia with traditional method of anesthesia, it was concluded that pressure anesthesia was more accepted and preferred by patients (70%) than traditional anesthesia (20%).…”
Section: Discussionmentioning
confidence: 99%
“…Anesthesia has also not provided a painless treatment for most anesthetized patients. In fact, full effectiveness is in general not reported and this is why new anesthetic drugs and techniques continue to be tested 8,19 . However, the situation was more severe in cases of nonsurgical procedures, given the presence of pain during the procedure as a whole and the fact that it was more severe when anesthesia was used.…”
Section: Discussionmentioning
confidence: 99%